Updating knowledge on the Critically Endangered white skate Rostroraja alba (Lacepède, 1803) through the first record in North-East Sardinian coastal waters - BELLODI, ANDREA; DI CRESCENZO, SIMONE; CARBONARA, PIERLUIGI; CROBE, VALENTINA; FERRARI, ALICE; MULAS, ANTONELLO; PORCU, CRISTINA; FOLLESA, MARIA CRISTINA; CANNAS, RITA (Mediterranean Marine Science, 2024)
The white skate Rostroraja alba has exhibited a declining trend similar to that of several large-bodied batoids in recent years. Consequently, it has been classified as Critically Endangered in European waters by the International Union for the Conservation of Nature. The presence of this species in Sardinian seas (central-western Mediterranean Sea) was recently hypothesised following the discovery of a hatched eggcase. Our findings confirmed this hypothesis through the discovery of another eggcase (this time unhatched) and, more importantly, the capture of an immature female (total length 131.2 cm) which was estimated to be 6 years old. Moreover, molecular analysis demonstrated that the new eggcase and the specimen did not share the same mother, thus suggesting the presence of a resident population, albeit likely small, of the species in the Sardinian seas.